2020
DOI: 10.1155/2020/6873891
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Type II Diabetes in a Large-Scale Chinese Population Using a Systematic Machine Learning Framework

Abstract: Background. An estimated 425 million people globally have diabetes, accounting for 12% of the world’s health expenditures, and the number continues to grow, placing a huge burden on the healthcare system, especially in those remote, underserved areas. Methods. A total of 584,168 adult subjects who have participated in the national physical examination were enrolled in this study. The risk factors for type II diabetes mellitus (T2DM) were identified by p values and odds ratio, using logistic regression (LR) bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…It was a good example of success for the XGBoost’s application in the research of diabetes risk prediction. This finding was consistent with earlier studies [ 14 , 21 , 27 , 53 ], which identified the good prediction power of the XGBoost model, with AUC values ranging from 0.8300 to 0.9680. Different from this study, a previous Korean population-based cohort study demonstrated that the ensemble models (e.g., stacking classifier) had better performance than the single models including XGBoost [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was a good example of success for the XGBoost’s application in the research of diabetes risk prediction. This finding was consistent with earlier studies [ 14 , 21 , 27 , 53 ], which identified the good prediction power of the XGBoost model, with AUC values ranging from 0.8300 to 0.9680. Different from this study, a previous Korean population-based cohort study demonstrated that the ensemble models (e.g., stacking classifier) had better performance than the single models including XGBoost [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…A potential reason could be due to the differences of the study population and input features in the models, which could impact the predictive performance to some extent. Different from our study, the study population of prior studies [ 14 , 21 , 27 , 53 ] were middle-aged adults and fewer predictors were applied in the prediction of diabetes. To our knowledge, this was the first study that targeted the elderly population (≥65 years) in China to build predictive models for diabetes using machine learning techniques, which would have great implications for designing diabetes prevention focusing on the elderly.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In both forecast periods, the XGBoost model performed relatively well. This was not unexpected; the predictive ability of XGBoost has manifested in previous studies of diabetes onset [17] and complications [18]. As an ensemble machine learning algorithm, XGBoost was not affected by the correlation of independent variables, which was exactly the problem that the LR model needed to solve.…”
Section: Discussionmentioning
confidence: 54%
“…It is difficult to use traditional logistic regression to process demographic and serological data which are often nonlinear, abnormal, and heterogeneous [ 9 ]. But machining learning (ML) provides a chance.…”
Section: Introductionmentioning
confidence: 99%